Nano-thin amorphous tantalum-coated prosthesis for acetabular bone defect reconstruction: in vivo study and case series - Chen, Chang; Wu, Siqi; Chen, Ge; Li, Zhong; Ma, Xiaofei; Wang, Fuyou (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe optimal reconstruction method for complex bone defects remains controversial. This study aims to introduce the innovative concepts of nano-thin tantalum coating titanium-based prostheses in treating complex acetabular bone defects.MethodTen minipigs were used for in vivo osseointegration test. Three types of scaffolds (TC4, pure Ta and Ta-coated TC4) were implanted in the femoral condyles, while Micro CT and histological staining were performed at 3 and 6 months post-operatively. Meanwhile, a prospective observational study was conducted from May 2023 to April 2024 to evaluate the clinical efficacy of TC4-based Ta-coated prostheses. The symptom relief and functional recovery were evaluated by visual analogue scale (VAS) and Harris hip score (HHS). Regular radiological follow-ups were arranged to monitor clinical outcomes.ResultsAll three types of scaffolds had satisfactory bone in-growth, while TC4 scaffolds still seemed inferior to pure Ta scaffolds and Ta-coated scaffolds in terms of early-stage bone in-growth rate. Totally 3 patients were enrolled in clinical series, with an average follow-up period of 21.7 months. All patients successfully underwent surgery. At the latest follow-up, all patients exhibited significant improvements in pain symptoms (as assessed by VAS) and HHS scores. No severe complications such as infection, prosthesis loosening, or vascular and nerve injuries were observed in any patient.ConclusionIn vivo experiments confirmed the Ta coating may contribute to enhanced osseointegration and biocompatibility of TC4-based prostheses. Meanwhile, the clinical efficacy of TC4-based Ta-coated prostheses in treating complex acetabular bone defects was satisfactory, suggesting that the tantalum coating significantly enhances osseointegration, thereby effectively improving clinical outcomes.